Conhecimentos de agentes comunitários de saúde e educadores acerca da alimentação e nutrição - Santiago, Nina Thais Gomes de Carvalho (2016)
The Community Health Agents (CHA) should encourage healthy lifestyles, developing educational actions aimed at health promotion and disease prevention. The Brazilian School Nutrition Program (Programa Nacional de Alimentação Escolar - PNAE) provides for the inclusion of food and nutritional education in the teaching-learning process through including the theme in the school curriculum, in a way that educators, as well as CHA, must act as knowledge multipliers and good health practices motivators in the school environment. However, the literature reveals that the knowledge of educators and CHA on food and nutrition is insufficient. This work contains one article with results and another article showing literature review. The second one aims to review the literature on the issue of promoting adequate and healthy food in schools, focusing on the importance of community health agent and educator as fundamental characters for these actions, covering the following topics: food and nutrition transition, breastfeeding and complementary feeding, health at school and educators and community health agents’ knowledge and practice of health. The article containing results aims to evaluate the knowledge of educators from five public early childhood centers (ECC) (Centros de Educação Infantil - CEI) as well as the education of Community Health Agents (CHA) of the five respective reference Basic Health Units (BHU) (Unidades Básicas de Saúde – UBS) located in the seventh health district of Maceió, about food and nutrition in the first two years of life and investigate the association with sociodemographic variables and professional performance. It is a cross-sectional study, developed with 10 educators of all early childhood centers (ECC), in the seventh district, in Maceio and community agents from renowned Basic Health Units (BHU), adding up to five early childhood centers and five basic health units. Self-administered questionnaires, previously tested, were applied in order to assess the educators and community agents’ knowledge on food and nutrition, the functioning of the School Health Program, as well as these professionals’ socioeconomic data. The chi-square test was used to investigate the presence of associations between selected variables, with significance level of p <0.05. The study results show that, in relation to breastfeeding, educators and community agents, 73% and 77.2%, respectively, answered the questions right. With regard to artificial feeding, the result was 66.8% and 77.2% of right answers. Regarding complementary feeding, they got 59% and 59.6%. Concerning to hygiene of food and utensils, the result was 50% and 50%, respectively, for sucessful answers. With respect to the total number of poll questions, 64.8% and 66.8% were answered right. It was concluded that actions are still needed to raise the studied professionals’ awareness on the this issue.